El malestar docente en los educadores oficiales de Bogotá D.C. entre el año 2005 y el 2015 - decreto 1278 de 2002 (2015)
"In this investigation, ""Oficial Teacher´s Burnout at Bogotá D.C, between years 2005 and 2015 - Decree 1278 from 2002, the problem called ""Teacher Burnout"", known as ""burnout"" as a result of the application of a rule: decree 1278, Teaching Professionalization Statute, issued in 2002, is approached. Such analysis begins from the comparison of the two existing statutes for the official magisterium, Decree 2279 (1979) and Decree 1278 (2002). Subsequently, the differences related to entrance, permanence, promotion and retirement are identified, to, finally, analyze the inequalities found to the view of the figures about working situations of the governmental teachers provided by Secretaría de Educación del Distrito. In spite of the limited information about the topic and of the lack of precise data, from the Secretaría de Educación as well as from the entities in charge of providing the medical services to the teachers, some findings are made that allow to identify that in governmental teachers of the Capital city exist an increasing degenerative dynamic of the working, professional and quality of life conditions, which are expressed on the high figures of: occupational discharges, disability retirements, resignations, dismissals, annulment declarations, ousters and designation revocations"